PENGARUH KINERJA SOSIAL DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PT. INDONESIA POWER - Muhammad Adil; Endang Winarsih (Magister Akuntansi, Universitas Atma Jaya Makassar, 2019)
This study aims to analyze the effect of disclosure of sosial performance and environmental performance on the financial performance of PT. Indonesia Power. The type of research used is a quantitative method that emphasizes the analysis of numerical data (numbers) processed by statistical methods. The processed data is a summary of financial performance data along with points of social performance and environmental performance with the calculation technique of the percentage of financial performance ratios measured by analysis of liquidity ratios, solvability, activity, and profitability. Data analysis method uses multiple regression techniques. The results of this study indicate that Sosial Performance and Environmental Performance have a simultaneous and partial significant effect on Financial Performance.